Characterization of ACC oxidase during leaf ontogeny in white clover (Trifolium repens L.) and Trifolium occidentale : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Du, Zhen-Ning (Massey University, 2004)
To produce plant material for this thesis, Trifolium repens (white clover) (genotype 10F) and Trifolium occidentale (genotype 18Z) were propagated to produce individual stolons trained over a plastic matrix to inhibit nodal root formation. These stolons comprised leaf tissue representative of all developmental stages, from leaf initiation, maturation through to senescence. The developmental pattern for both species in terms of leaf ontogeny was generally reproducible between vegetatively propagated clones. Three distinct 1-aminocyclopropane-1-carboxylatc (ACC) oxidase genes expressed during leaf ontogeny in white clover (Trifolium repens L.) have been identified (Hunter et al., 1999). Of the three ACC oxidase genes identified, one designated TR-ACO2 is expressed in newly initiated and mature green leaves while TR-ACO3 is expressed predominantly in the senescent leaf tissue. In order to further characterize the protein products of these genes, a series of FPLC columns was used to partially purify isoforms of ACC oxidase from leaf tissue of white clover at different developmental stages, followed by 2D gel electrophoresis to obtain further purification. Two distinct isoforms of ACC oxidase were identified and partially purified from newly initiated green (designated the NIGI isoform) and senescent (designated the SEI isoform) leaf tissue. Both purified NIGI and SEI proteins were recognized by western analysis using an anti-(Trifolium repens) TR-ACO2 antibody after SDS-PAGE or 2D gel electrophoresis. To determine whether NIGI is coded for by TR-ACO2 and SEI is coded for by gene TR-ACO3, protein spots (after 2D gel electrophoresis) were digested with trypsin and the masses of the peptide determined by matrix-assisted laser desorption ionization-timc of flight (MALDI-TOF) mass spectrometric analysis. For NIGI, the coverage of the putative protein sequence (TR-ACO2) by tryptic digestion ranged from 24.5% to 37.6%, while the observed pI (5.1) and molecular mass (37 kDa) were close to the theoretical pI (5.3) and computed mass (35.7 kDa). For SEI, the percentage coverage of the putative protein sequence (TR-ACO3) from the peptides identified ranged from 13.4% to 18.0%, while the observed pI (5.2) and molecular masses (35.0-35.5 kDa) were also close to the theoretical pI (5.5) and computed mass (35.2 kDa). These data suggest that the NIGI isoform is encoded by TR-ACO2, while the SEI isoform is encoded by TR-ACO3. ACC oxidase activity in vitro and ACC oxidase protein accumulation over 24 h in mature green leaf tissue extracts during both short and long days has been shown to be under circadian control. There are two ACC oxidase activity peaks observed, in which the pattern of fluctuation in ACC oxidase activity resulted in a high level of enzyme activity at 12:00 am (0.18-0.27 nmol ethylene/h/mg), and maximum activity at 12:00 pm (0.24-031 nmol ethylene/h/mg). Lowest activity was observed in both long and short days at 9:00 pm (0.09-0.10 nmol ethylene/h/mg). In addition, northern analysis indicated that the TR-ACO2 mRNA level also displayed a circadian pattern of expression. Investigation of the effect of protein phosphorylation and dephosphorylation on ACC oxidase activity indicated that ACC oxidase activity in vitro during the periods of maximum activity increased 36% (at 12:00 am) and 56% (at 12:00 pm) after dephosphorylation, respectively. However, there was only 21% increase in enzyme activity at the time point with lowest activity (9:00 pm) in the dephosphorylated extracts. SDS-PAGE using a mini-protein gel system or a gradient gel system showed that the molecular mass of ACC oxidase decreased after dephosphorylation when compared with phosphorylation of the enzyme. These results suggest that the phosphorylation and dephosphorylation of the ACC oxidase proteins occurs in vitro and the state does affect enzyme activity. In the second part of this thesis, the coding regions of putative ACC oxidase gene transcripts were generated from leaf tissue of genotype 18Z of T. occidentale using RT-PCR. Sequence alignments indicated that the sequences could be grouped into two distinct classes, and these coding regions were designated TO-ACO2 (Trifolium occidentale ACC oxidase 2) and TO-ACO3 (Trifolium occidentale ACC oxidase 3). TO-ACO2 and TO-ACO3 share 82% similarity in nucleotide sequence and 84% similarity in amino acid sequence. The TO-ACO2 and TO-ACO3 sequences were validated as encoding ACC oxidases by comparison with other ACC oxidases in the GenBank database and both TO-ACO2 and TO-ACO3 deduced amino acid sequences contain all the residues hitherto shown to be important for maximal activity of the enzyme. Further, TO-ACO2 had 97% identity with TR-ACO2 at the nucleotide level, and 98% identity at the amino acid level. TO-ACO3 had 97% identity with TR-ACO3 at the nucleotide level, and 96% identity at the amino acid level. Genomic Southern analysis, using 3'-UTRs of TR-ACO2 and TR-ACO3 as probes, could not confirm that TO-ACO2 and TO-ACO3 arc encoded for by distinct genes. Expression studies of TO-ACO2 and TO-ACO3 genes during leaf maturation and senescence of T. occidentale were examined using northern analysis. TO-ACO2 is expressed predominantly in newly initiated and at the onset of the mature-green leaf stage, while TO-ACO3 shows maximal expression in senescent leaf tissue. The changes of ACC oxidase activity during leaf ontogeny of T. occidentale coincided with the pattern observed for ACC oxidase protein accumulation using western analysis and image analysis.
Keywords: Leaf growth; Oxidase genes; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300300 Horticulture::300302 Plant growth and development